Novel ion channel targets in atrial fibrillation - Hancox, Jules C.; James, Andrew F.; Marrion, Neil V.; Zhang, Henggui; Thomas, Dierk (Expert opinion on therapeutic targets, 2016)
Introduction: Atrial fibrillation (AF) is the most common arrhythmia in humans. It is progressive and the development of electrical and structural remodeling makes early intervention desirable. Existing antiarrhythmic pharmacological approaches are not always effective and can produce unwanted side effects. Additional atrial-selective antiarrhythmic strategies are therefore desirable.Areas covered: Evidence for three novel ion channel atrial-selective therapeutic targets is evaluated: atrial-selective fast sodium channel current (INa) inhibition; small conductance calcium-activated potassium (SK) channels; and two-pore (K2P) potassium channels.Expert Opinion: Data from animal models support atrial-ventricular differences in INa kinetics and also suggest atrial-ventricular differences in sodium channel β subunit expression. Further work is required to determine whether intrinsic atrial-ventricular differences in human INa exist or whether functional differences occur due to distinct atrial and ventricular action and resting potentials. SK and K2P channels (particularly K2P 3.1) offer potentially attractive atrial-selective targets. Work is needed to identify the underlying basis of SK current that contributes to (patho)physiological atrial repolarization and settings in which SK inhibition is anti- versus pro-arrhythmic. Although K2P3.1 appears to be a promising target with comparatively selective drugs for experimental use, a lack of selective pharmacology hinders evaluation of other K2P channels as potential atrial-selective targets.